Pagan Religious Practices in Medieval Ethiopia: Development and Resistance of the Christian Kingdom (1434–1468) - Solomon Gebreyes Beyene (Entangled Religions - Interdisciplinary Journal for the Study of Religious Contact and Transfer, 2022)
In the long religious history of Ethiopia, paganism has been widely practised since ancient times, as evidenced by the inscriptions of ʿEzānā and other archaeological objects. It continued to dominate for centuries even after the introduction of Christianity in the fourth century, which hindered its expansion south of the Aksumite empire until the thirteenth century. However, later in the fourteenth century, Christianity was widely expanded with the military and political support of the Christian emperors, especially King ʾAmda Ṣǝyon (1314–1344), who suppressed pagan practices in the northern highlands of the Christian kingdom. Subsequently, pagan chiefs and priests were forced to be baptised and converted to Christianity, pagan sanctuaries were dismantled, and, in their place, churches and monasteries were built. Resistance against paganism continued in a more organised way in the fifteenth century during the reign of King Zarʾa Yāʿǝqob (1434–1468), who actively engaged in making laws and composing religious books to prevent Christian adherents from practising paganism. In this regard, we have a sizeable collection of Gǝʿǝz texts dating to the time of Zarʾa Yāʿǝqob that provide vivid information to better understand the development and features of paganism, on the one hand, and the measures undertaken by the king as a part of religious reformation to resist and dismantle pagan practices, on the other. Paganism, in general, is a neglected subject in the historiography of medieval Ethiopia, but taking into account the source availability, studying the pagan practices and resistance of this period is indispensable. Thus, this paper attempts to reconstruct the history of pagan practices and its development in the period under discussion to identify the names of the pagan gods as well as to analyse their social role and the measures taken under Zarʾa Yāʿǝqob against paganism.